If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(4s + 7) = 385 Reorder the terms: 7(7 + 4s) = 385 (7 * 7 + 4s * 7) = 385 (49 + 28s) = 385 Solving 49 + 28s = 385 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + 28s = 385 + -49 Combine like terms: 49 + -49 = 0 0 + 28s = 385 + -49 28s = 385 + -49 Combine like terms: 385 + -49 = 336 28s = 336 Divide each side by '28'. s = 12 Simplifying s = 12
| 17-3x=-1 | | (3x+5)(2x-12)=0 | | 6(x+1)=90 | | (5x+3)(x+6)=0 | | 4(a-1)=84 | | (x-6)(x^2-3x+4)= | | (5x+3)(x-6)=0 | | Log(2x-4)=4 | | (3x-5)(x-6)=0 | | 8x=(13x+3) | | (X*40)+(x*1.5*10)=923 | | 8x=13x+3 | | x+x-6=47 | | 4(r=20)=1/5(20r=400) | | 5x-3(2-1x)=1-2x | | 4x^2-3x+7=11 | | 2(a+b)-10= | | x=2y+3w | | 2(AB)-10= | | x^3+6x^2-36=0 | | 2(A*B)=10 | | x^3+6x^2-36=30 | | (2x+2)(5x^2+3x-2)= | | 5+x=x*2.37500 | | 10x^2+-21=0 | | 2x*x^2=6 | | e^5x-9=12 | | 6+12(10-x)=84 | | j-63/2=2 | | 3+(x-2)-3x=3(4x-2) | | -46-(-34)=X/4 | | 7x-4(x-3)=2y |